Hegemony of real estate capital in the (re)production of space in the Atlantic coastal area of Salvador, Bahia, Brazil, between 2006 and 2018 - Mariana de Oliveira Santana; Maina Pirajá Silva (Geografares, 2023)
Real estate capital has shown great dynamics in the (re)production of Brazilian urban spaces, especially in recent decades. In Salvador, the Atlantic coastal area stands out in this process, as in addition to being one of the main vectors of growth, it is an area aimed at the middle and upper income classes. In this sense, this study aimed to analyze the (re)production of space in the coastal area in Salvador, between 2006 and 2018. This is a period that includes changes to the city’s master plans and major changes in the coastal area, in addition to the actions of different agents involved in the process. The article is based on a qualitative and quantitative approach, using historical and comparative methods. The main results showed that real estate capital is the main agent of the (re)production of space in the city, as well as a heterogeneous but hegemonic group of private agents, and that the city space is being (re)developed with a view to the interests of these agents.